World Heritage Listing: Blessing or Curse? - Zhang, Yifan (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
The World Heritage List, managed by UNESCO, aims to identify and protect sites of significant cultural and natural value. While inclusion on this list can enhance a site’s visibility, attract tourism, and secure funding for preservation, it also presents challenges such as excessive tourists and excessive commercialization. This paper explores the dual nature of World Heritage listing by examining its benefits and drawbacks. Case studies, including Rapa Nui, George Town, Malacca, Lijiang, and Mont Saint-Michel, highlight the complex impact of this designation. The paper concludes that the impact of a site’s inclusion on the World Heritage List is complex and cannot be simply categorized as a blessing or a curse. To maximize the benefits of World Heritage listing while mitigating its adverse effects, a balanced approach to site management is essential.